Pediatric airway tumors: A report from the International Network of Pediatric Airway Teams (INPAT). (15th May 2019) - Pio, Luca; Varela, Patricio; Eliott, Martin J.; Couloigner, Vincent; Guillén Burrieza, Gabriela; Paraboschi, Irene; Virgone, Calogero; Maunsell, Rebecca; Rachkov, Victor; Rutter, Michael J.; Boglione, Mariano; Penchyna Grub, Jaime; et al.
Abstract : Objective: Primary tracheobronchial tumors (PTTs) are rare heterogeneous lesions arising from any part of the tracheobronchial tree. Nonspecific symptoms may lead to delayed diagnosis that requires more aggressive surgical treatment. An analysis of cases collected by the International Network of Pediatric Airway Team was undertaken to ensure proper insight into the behavior and management of PTTs. Methods: Patients <18 years of age with a histological confirmation of PTT diagnosed from 2000 to 2015 were included in this multicenter international retrospective study. Medical records, treatment modalities, and outcomes were analyzed. The patient presentation, tumor management, and clinical course were compared between malignant and benign histotypes. Clinical and surgical variables that might influence event‐free survival were considered. Results: Among the 78 children identified, PTTs were more likely to be malignant than benign; bronchial carcinoid tumor (n = 31; 40%) was the most common histological subtype, followed by inflammatory myofibroblastic tumor (n = 19; 25%) and mucoepidermoid carcinoma (n = 15; 19%). Regarding symptoms at presentation, wheezing ( P = 0.001) and dyspnea ( P = 0.03) were more often associated with benign growth, whereas hemoptysis was more frequently associated with malignancy ( P = 0.042). Factors that significantly worsened event‐free survival were age at diagnosis earlier than 112 months ( P = 0.0035) and duration of symptoms lasting more than 2 months ( P = 0.0029). Conclusion: The results of this international study provide important information regarding the clinical presentation, diagnostic workup, and treatment of PTTs in children, casting new light on the biological behavior of PTTs to ensure appropriate treatments. Level of Evidence: NA Laryngoscope, 130:E243–E251, 2020